Advanced assessment through intact glycopeptide analysis of Infliximab’s biologics and biosimilar - Kim, Hyejin; Bang, Geul; Park, Ye Eun; Park, Moonhee; Choi, Jung Hoon; Oh, Myung Jin; An, Hyun Joo; Yoo, Jong Shin; Park, Youngja Hwang; Kim, Jin Young; Hwang, Heeyoun (Frontiers in Molecular Biosciences, 2022)
Characterization of therapeutic monoclonal antibodies (mAbs) represents a major challenge for analytical sciences due to their heterogeneity associated with post-translational modifications (PTMs). The protein glycosylation requires comprehensive identification, which could influence on the mAbs’ structure and their function. Here, we demonstrated high-resolution tandem mass spectrometry with an ultra-high-performance liquid chromatography for characterization and comparison between biologics and biosimilar of infliximab at an advanced level. Comparing the N- and O-glycopeptides profiles, a total of 49 and 54 glycopeptides was identified for each product of the biologics and biosimilar, respectively. We also discovered one novel N-glycosylation site at the light chain from both biopharmaceuticals and one novel O-glycopeptide at the heavy chain from only biosimilar. Site-specific glycopeptide analysis process will be a robust and useful technique for evaluating therapeutic mAbs and complex glycoprotein products.